Discourse particles syntactic, semantic, pragmatic and historical aspects - Artiagoitia, X. (Xabier); Elordieta, Arantzazu; Monforte, Sergio (Linguistik aktuell ;, 2022)
"Discourse particles have often been treated as a phenomenon restricted to Germanic languages (Abraham 2020) and they still raise questions about their nature as an independent category. This book reveals that this phenomenon exists in other languages as well, and provides evidence for their nature as a separate category. The volume brings together a collection of nine papers that focus on three research topics: a) the diachronic development of discourse particles; b) their syntactic analysis; and c) the study of their semantic-pragmatics. Furthermore, it also discusses other issues less dealt with in the literature but of great interest for linguistic theory, such as the acquisition of discourse particles by children or the analysis of elements not usually considered discourse particles but whose historical path or microvariation indicates otherwise. Additionally, the book offers a cross-linguistic perspective as it discusses various languages including Basque, Catalan, German, Italian, Laz, Mandarin Chinese, Old English, Portuguese, and Spanish"--